Jealousy in Men and Women in Couples Infidelity through Online Media - Yana, Wayan Karang; Melinda, Esti (JASSP, 2023)
Every human being in this world has a jealous attitude that has been felt by both men and women. In the younger generation which is a generation in the early stages of maturity jealousy often occurs especially for young couples who are in a dating relationship. Jealousy usually occurs due to a partner affair done through online media or the use of the internet as a medium to communicate with third people. This study aims to find out the extent to which differences in jealousy in men and women that are consistently found in real life can also be found in modern life which involves the use of internet technology. The method used in this research is a quantitative research method. This research was conducted in Indonesia by involving young people in it. In taking the research sample, several characteristics of the participants had to be met, including participants aged 20 to 40 years, single, had at least a high school education, and used the internet for at least 7 hours per week. The results showed that there was a significant difference in female participants in jealousy facing emotional and sexual types of infidelity via the internet and vice versa. In addition, the majority of people in Indonesia, especially young people or students in Indonesia, use social media, and jealousy between partners is often expressed on social media, and young people in Indonesia are easily influenced by the times